Miami, the magic city - Parks, Arva Moore, 1939-; Brooke, Steven; Born, Donna Knowles (Miami, Florida : Centennial Press, 1991)
Un comentario pictórica y entretenido en el crecimiento y desarrollo de Miami, Florida.
La Florida. Bloody red, white and blue. Carpetbaggers and homesteaders. Never a town. The magic city. Boom, bust and blow. The morning after. Getting ready. New world center. City of the future. Partners in Miami's progress. Bibliography. Index. Credits.
"The official history of the city of Miami." - En la cubierta y portada.
Incluye referencias bibliográficas (páginas 248-249) e índice..
Keywords: MIAMI (FLORIDA, ESTADOS UNIDOS) -- INDUSTRIAS; MIAMI (FLORIDA, ESTADOS UNIDOS) -- HISTORIA; MIAMI (FLORIDA, ESTADOS UNIDOS) -- VIDA SOCIAL Y COSTUMBRES